The Luminescence of CH3NH3PbBr3 Perovskite Nanoparticles Crests the Summit and Their Photostability under Wet Conditions is Enhanced. Issue 38 (24th August 2016) - Gonzalez‐Carrero, Soranyel; Francés‐Soriano, Laura; González‐Béjar, María; Agouram, Saïd; Galian, Raquel E.; Pérez‐Prieto, Julia
Abstract : CH3 NH3 PbBr3 perovskite nanoparticles (PAD ) are prepared with a photoluminescence quantum yield of ≈100% in air atmosphere by using the quasi‐spherical shaped 2‐adamantylammonium bromide (ADBr) as the only capping ligand. The photostability under wet conditions of this kind of nanoparticles is enhanced by using cucurbit[7]uril‐adamantylammonium (AD@CB) host–guest complexes as the capping ligand.